Walk back tuning and paper tuning: How do they improve archery accuracy? - Yacshie, Betrix Teofa Perkasa Wibafiet Billy; Prasetyo, Yudik; Arianto, Afeb Chesa (Journal Sport Area, 2022)
Limited knowledge to determine the use and purpose of the two tunings has not been proven by scientific research. Research to find precise tuning for standard bow, recurve, and compound rounds to improve archery accuracy. This type of research is quantitative experimental research with a two-group pretest posttest design. The sample consists of 24 athletes who are given treatment in 16 meetings. The instrument used is a test scoring archery at a distance of 40m. The collected data will be tested for normality using the Kolmogorov Smirnov technique and the homogeneity test using the Levene statistic technique with a significant level of 5% (p>0.05). Hypothesis testing uses paired samples t-test technique. The results this study indicate (a) there is an effect of walk back tuning increasing archery accuracy of archery athletes, (b) there is an effect of paper tuning training increasing archery accuracy of archery athletes, (c) there is different effect between walk back tuning and paper tuning increasing archery accuracy of archery athletes, where walk back tuning exercises have a greater effect on increasing archery accuracy in archery athletes. This research is expected to be source of reference for athletes and coaches to explore the bow tuning method.